Leptoderma macrophthalmum n.sp., a new species of smooth-head (Otocephala: Alepocephalidae) from the Mid Atlantic Ridge - Byrkjedal, Ingvar; Poulsen, Jan Yde; Galbraith, John (Zootaxa, 2011)
A new species of Alepocephalidae, Leptoderma macrophthalmum n.sp., is described from one specimen caught in 2004 at about 2100 m depth at the Mid Atlantic Ridge, north of the Azores. Morphological and molecular evidence indicate a relationship closest to the Pacific species Leptoderma lubricum.